Diels–Alder functionalized carbon nanotubes for bone tissue engineering: in vitro/in vivo biocompatibility and biodegradability1. Issue 20 (28th May 2015) - Mata, D.; Amaral, M.; Fernandes, A. J. S.; Colaço, B.; Gama, A.; Paiva, M. C.; Gomes, P. S.; Silva, R. F.; Fernandes, M. H.
<x xml:space="preserve">Abstract</x> Diels–Alder functionalization accounts for the improved CNT biological response in terms of biocompatibility and biodegradability profiles.